(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The paper describes the methodology of business game "Enterprise Taxation" for Customs tax service students training. The purpose of the game, its task, an approximate duration and stages of the game are explained in the work. The author determines the distribution of auditorium time for each stage of the game and proposes an algorithm for its conduct. The method of the game provides solving following professional problems by Customs tax service students: choice of optimal taxation option strategy; correct use of current legislative and normative tax documentation; selection of tax reporting forms (tax returns); preparation of tax documentation. Proposed methodology for game organizing promotes the development of special competencies of students while studying and subjects of small entrepreneurship engaged in self-education.